Currículo e Base Nacional Comum Curricular: o processo de implementação na rede estadual paulista - Nascimento, Rodrigo Rios (2020)
This research aims to analyze the Brazilian learning standards known as Base Nacional Comum Curricular (BNCC) – following as a normative document that guides the formulation of curricula - and its implementation process in the public education network of the state of São Paulo, as well as the elaboration of the São Paulo curriculum (CP), which emerged as its unfolding. The theoretical reference is based in Sacristan (2017), which understands the curriculum in a procedural dimension, that links practices and configures them, presenting curricular concepts such as cultural selection, the prescribed curriculum and the curriculum offered to teachers. The method included a documentary survey (Gil, 2007) based on the BNCC and the Curriculum of the State of São Paulo, and the analysis of semi-structured interviews with teachers, managers of school boards and public schools. It is based on the textual discursive review (Moraes and Galiazzi, 2016) to understand the interviewees ' lines on aspects of BNCC and CP. It was possible to observe that BNCC, as a normative document, can guide the formulation of regional curricula, as mentioned in CP confirming the hypothesis of this investigation; and have implications on the production of educational material that supervises the pedagogical practice, by the Programa Nacional do Livro e do Material Didático (PNLD). In conclusion, the process of implementation in the public education network of the state of São Paulo may not be satisfactory in virtue of the comprehension and expectations from some educational agents about the BNCC and the CP, itself. However, the topic has high relevance in the Brazilian education scenario because it is a latent and urgent topic, considering that the BNCC will have implications in the (re)reorganization of regional and local curricula in a country with great regional diversities. This research aims to analyze the Brazilian learning standards known as Base Nacional Comum Curricular (BNCC) – following as a normative document that guides the formulation of curricula - and its implementation process in the public education network of the state of São Paulo, as well as the elaboration of the São Paulo curriculum (CP), which emerged as its unfolding. The theoretical reference is based in Sacristan (2017), which understands the curriculum in a procedural dimension, that links practices and configures them, presenting curricular concepts such as cultural selection, the prescribed curriculum and the curriculum offered to teachers. The method included a documentary survey (Gil, 2007) based on the BNCC and the Curriculum of the State of São Paulo, and the analysis of semi-structured interviews with teachers, managers of school boards and public schools. It is based on the textual discursive review (Moraes and Galiazzi, 2016) to understand the interviewees ' lines on aspects of BNCC and CP. It was possible to observe that BNCC, as a normative document, can guide the formulation of regional curricula, as mentioned in CP confirming the hypothesis of this investigation; and have implications on the production of educational material that supervises the pedagogical practice, by the Programa Nacional do Livro e do Material Didático (PNLD). In conclusion, the process of implementation in the public education network of the state of São Paulo may not be satisfactory in virtue of the comprehension and expectations from some educational agents about the BNCC and the CP, itself. However, the topic has high relevance in the Brazilian education scenario because it is a latent and urgent topic, considering that the BNCC will have implications in the (re)reorganization of regional and local curricula in a country with great regional diversities.